Description of three new species of Neoperla (Plecoptera: Perlidae) and a historical review of tropical Southeast Asian Perlidae - Cao, Thi Kim Thu; Ham1, Soon Ah; Bae, Yeon Jae (Zootaxa, 2007)
The stonefly family Perlidae has successfully invaded tropical Southeast Asian streams. In this paper, three new species of Neoperla Needham, N. sungi, sp. nov., N. tamdao, sp. nov., and N. yentu, sp. nov., are described from tropical Vietnam with line drawings of key characters. A brief historical review of investigations and trends in tropical Southeast Asian Perlidae diversity, including a species checklist, is provided.